Generalized pseudo Ricci symmetric manifolds with semi-symmetric metric connection - DEMIRBAG, SEZGIN ALTAY (Kuwait Journal of Science, 2014)
In this paper, firstly an example of a manifold with almost constant curvature and nearly quasi constant curvature which is neither quasi Einstein nor nearly quasi Einstein is given. Later, the existence of a generalized pseudo Ricci symmetric manifold is proven by a nontrivial concrete example by using Exp-function Method and Differential Transform Method.